King Solomon's mines - Haggard, H. Rider (Henry Rider), 1856-1925.; Langford, Alan (New York : Puffin, 1994)
The story of three men who trek to the remote interior of Africa in search of a lost friend. At the end of their perilous journey, they find their friend and the spectacular diamond mines of King Solomon.
Wilson's Fiction.
Wilson's Senior High School.
7.0
Young Adult
Keywords: Adventure and adventurers -- Africa -- Fiction; Missing persons -- Africa -- Fiction; Treasure troves -- Africa -- Fiction; Adventure fiction; Buried treasure -- Fiction; Missing persons -- Africa -- Fiction; South Africa -- Fiction